La transformation de la politique sur Internet : de la politique-spectacle à la cyberdémocratie d’activisme citoyen - José Luis Dader (Netcom)
The New Technologies of Information and Communication (ICT’s) applied to the political communication are provoking a profound conversion into the realm of politics of the most developed societies. A lot of the new tools of what it starts to be called “technopolitics” only add bigger sensationalism, sentimentalism and triviality to the portrayal of leaders, political parties and governs. The political videos in Youtube, the viral marketing and the twitter-craziness boost the political hype impact but they only strength, most of the times, the propagandist distortion instead of the analysis of electoral proposals and the basic data of policy management. However, those same technologies facilitate the emergence of new public places of social scrutiny, deliberation and aware monitoring of political matters, thanks to civic movements who take advantage of cybernetic empowerment to advance through a “Democracy 2.0” or a progressive “Cyberdemocracy”. A selection of examples of those opposite trends will permit to understand the lights and shadows of the Internet environment in the new political communication.